Examining the Relationship Between Problematic Social Media Use and Dark Personality Traits with the Mediating Role of Emotion Regulation and Self-Compassion in Adult Instagram Users in Tehran - Jamshidi, Sara; Noferesti, Azam; Farahani, Hojjatollah (Health Nexus, 2024)
Despite the information dissemination and communication facilities provided by these networks, they have also brought about damages. The purpose of the current research is to investigate the relationship between problematic social media use and dark personality traits with the mediating role of emotion regulation and self-compassion among adult Instagram users in Tehran. The methodology of this study is descriptive-correlational, employing a structural equation modeling approach. The population of the study consisted of all adult Instagram users (ages 18 to 80) in Tehran in the year 2022. The sample size was 306 individuals, selected through convenience sampling. The questionnaires used in this research were the Mobile Social Networking Addiction Questionnaire by Khajeh Ahmad and colleagues (2016), Dark Personality Traits by Jonason and Webster (2010), Emotion Regulation by Gratz and Roemer (2004), and Self-Compassion by Neff (2003). Analysis of the findings was conducted using structural equation modeling by AMOS-22. Findings showed that problematic social media use among adult Instagram users has a positive and significant relationship with dark personality traits (P